Study of sound absorptions by using acoustic impedance tube - Saabiq Al-Ahsin Haji Ja'afar (2017)
Sound absorption is one of the main components in acoustics and engineers need to know the sound absorption properties of the material before it can be used in the design. One of the common quantities used for the measurement of sound absorption is the sound absorption coefficient which is defined as the ratio of energy absorbed by the material to the energy incident upon its surface. In theory, part of the absorbed energy will be transformed to heat. Hence, the focus of this project is to study the sound absorption of heat absorbers, to see if good heat absorption does equate to good sound absorption, with a Brüel & Kjær Two Microphone Impedance Tube Type 4206. The samples of interest are 3D printed membrane absorbers, micro perforated plate absorbers of different materials and micro-perforated plate backed with corrugated board of different corrugation size. In the end, the 3D printed membrane absorbers resulted in a low sound absorption coefficient and works better in the lower frequency ranges while reducing the corrugation size increases the resonant peak and shifts the resonant peak to a higher frequency. However, the effects of using different materials for the micro-perforated plate proved inconclusive. Discussion of the design of the test samples, experimental setups and experimental results are presented in this report.